Histology results of systematic prostate biopsies by in-bore magnetic resonance imaging vs. transrectal ultrasound - Lazarovich, Alon; Raviv, Gil; Laitman, Yael; Portnoy, Orith; Raz, Orit; Dotan, Zohar A.; Ramon, Jacob; Rosenzweig, Barak (Canadian Urological Association Journal, 2020)
Introduction: We aimed to compare systematic biopsies (SBs) of in-bore magnetic resonance-guided prostate biopsy (MRGpB) with those performed under transrectal ultrasound (TRUS) guidance in the clinical setting. Methods: Data on all 161 consecutive patients undergoing prostate biopsy at our institution between November 2017 and July 2019 were retrospectively collected. The patients were referred to biopsy due to elevated prostate-specific antigen (PSA) and/or abnormal digital rectal examination (DRE) and/or at least one Prostate Imaging Reporting and Data System (PI-RADS) lesion score of ≥3 on multiparametric magnetic resonance imaging (mpMRI). We included patients with PSA levels ≤20 ng/ml and those with 8–12 core biopsies. Histology results of SBs performed by in-bore MRGpB were compared to TRUS SBs. Chi-squared, Fischer’s exact, and multivariate Pearson regression tests were used for statistical analysis (SPSS, IBM Corporation). Results: In total, 128 patients were eligible for analysis. Their median age was 68 years (interquartile range [IQR] 61.5–72), mean prostate size 55±29 cc, and mean PSA and PSA density levels 7.6±3.5 ng/ml and 0.18±0.13 ng/ml/cc, respectively. Thirty-five patients (27.3%) had suspicious DRE findings. Both biopsy groups were similar for these parameters. Thirty-eight (62.3%) MRGpB patients had a previous biopsy vs. five (7.1%) TRUS-SB patients (p<0.0001). The number of patients diagnosed with clinically significant and non-significant disease was similar for both groups. High-risk disease was more prevalent in the TRUS-SB group (22.4% vs. 4.9%, p<0.01). Conclusions: Our data suggest that in-bore MRGpB is no better than TRUS for guiding SBs for the detection of clinically significant prostate cancer.